Targeting miR-148b-5p Inhibits Immunity Microenvironment and Gastric Cancer Progression - Zhang, Yuyu; Huo, Wei; Sun, Lidi; Wu, Jie; Zhang, Chengbin; Wang, Huanhuan; Wang, Bin; Wei, Jinlong; Qu, Chao; Cao, Hongshi; Jiang, Xin (Frontiers in Immunology, 2021)
Background MicroRNAs (miRNAs) have been discovered to dictate the development of various tumors. However, studies on the roles of miRNAs in the progression of gastric cancer (GC) are still lacking. Methods Herein, by analyzing GC cell lines and patients samples, we observed that miR-148b-5p was significantly downregulated in GC. We also confirmed that miR-148b-5p overexpression significantly inhibited GC cell proliferation and invasion in vitro and in vivo. Results Overexpression of miR-148b-5p not only reprogrammed the metabolic properties of GC but also regulated the immune microenvironment by shifting lymphocyte and myeloid populations. Mechanistically, ATPIF1, an important glycolysis-associated gene, was identified as a direct target of miR-148b-5p and mediated the effect of miR-148b-5p. Notably, the low level of miR-148b-5p was significantly related with poor prognosis of GC patients (P < 0.001). Importantly, the levels of miR-148b-5p significantly changed the sensitivity of GC cells to several anti-cancer drugs (Doxorubicin, P < 0.05, Paclitaxel, P < 0.01, Docetaxel, P < 0.05). Conclusions Targeting miR-148b-5p inhibits immunity microenvironment and gastric cancer progression.